2020
DOI: 10.1021/acsomega.0c04076
|View full text |Cite
|
Sign up to set email alerts
|

Ho and Ti Co-Substitution Tailored Structural Phase Transition and Enhanced Magnetic Properties of BiFeO3 Thin Films

Abstract: The polycrystalline thin films of BiFeO3 (BFO) and Bi0.90Ho0.10Fe1–xTixO (x = 0, 0.025, 0.05, 0.10, 0.15, and 0.20) were successfully synthesized by the simple sol–gel method. X-ray diffraction and Raman spectra revealed the substitution of Bi and Fe by Ho and Ti, respectively, and correspondingly a structural phase transition from the rhombohedral phase to orthorhombic phase. The field-emission scanning electron microscopy and transmission electron microscopy images indicated that the average size of the part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Prevailing literature indicates that both Fe 3+ and Fe 2+ ions coexist within BFO matrices [19,29]. The Fe 2+ ion is known to contribute to magnetic anisotropy, whilst the Fe 3+ ion is anticipated to exhibit isotropic behavior due to its electronic configuration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevailing literature indicates that both Fe 3+ and Fe 2+ ions coexist within BFO matrices [19,29]. The Fe 2+ ion is known to contribute to magnetic anisotropy, whilst the Fe 3+ ion is anticipated to exhibit isotropic behavior due to its electronic configuration.…”
Section: Resultsmentioning
confidence: 99%
“…This particular substitution was chosen because the ionic radius of Ti 4+ (0.645 Å) closely approximates that of Fe 3+ (0.645 Å), which favors a distorted rhombohedral symetry with an R3c space group and facilitates significant polarization along the [001] hexagonal or [111] pseudocubic direction [17]. Furthermore, it is anticipated that substituting Fe 3+ with Ti 4+ would decrease the leakage current density and enhance the ferroelectric properties of BFO [18] Ti 4+ acts as a donor within the oxygen octahedra framework, mitigating oxygen vacancy formation, and preventing the valence fluctuation from Fe 3+ to Fe 2+ [19]. Prior investigations into Ti 4+ substitution for Fe 3+ have demonstrated that lattice strains and defects, resultant from the disparity in ionic radii, inhibit grain growth as the level of substitution increases.…”
Section: Introductionmentioning
confidence: 99%
“…These saturation magnetization values are consistent with earlier reported studies. [19,20] In bulk BFO, the spiral arrangements of magnetic spins with a wavelength of 62 nm tend to suppress magnetization. [1][2][3] However, in small particles, this periodicity of spin cycloid can be disrupted as their size decreases to 62 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Bismuth ferrites, a large group of transition-metal oxides, including perovskite, mullite, and sillenite-type structural compounds have lately sparked the interest of researchers due to their superior fundamental physics and wide-ranging technological applications. , Among them, perovskite-type BiFeO 3 (BFO) with a suitable band gap of ∼2.2 eV and the existence of simultaneous ferroelectric and ferromagnetic ordering at room temperature is mostly studied in the field of visible-light responsive photocatalysis . Compared to perovskite BFO, the synthesis and analysis of other phases such as sillenite-type Bi 25 FeO 40 with the I 23 cubic crystal structure are yet less explored. , The sillenite compounds, bearing the general formula of Bi 12 MO 20 (M = Ge, Ti, Ga, Fe, Bi, V, etc), exhibit unique properties such as photo-refractivity, optical activity, and photo-conductivity .…”
Section: Introductionmentioning
confidence: 99%